ЭКОЛОГИЧЕСКОЕ ЗНАНИЕ И ФУТУРОЛОГИЯ В КОНТЕКСТЕ НАУКИ И ВОПРОСОВ УПРАВЛЕНИЯ - Годзь, Н. Б. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Экология в глобальном понимании шире просто природоохранных технологий. В целом,экологию как науку определяет интерес параметров роста, пределов существования, анализпопуляций и пищевых цепочек. Можно сказать, что экология, это наука про систему, кактаковую. Но придание новых смыслов и содержаний играет не только положительную роль, но иотрицательную, создавая поле конфликтов, в основании которого может лежать разноепонимание предмета и объекта экологии, что опасно приводит к демагогии и сверхупрощению.Настаиваем на необходимости вслед за рассмотрением и упорядочиванием системыэкологического знания, ввести такой концепт, как «Экологическая футурология», черезиспользование которого может быть отражена вся полнота практических и теоретическихстратегий будущего.Ключевые слова: Гиперсистема, Экология, Философия экологии, Футурология,Экологическая футурология, История науки и техники, Техника, Социосфера, «Потребительскоесуществование», Конфликт.Годзь Н.Б. Екологічне знання та футурологія в контексті науки та питань управління.Екологія у глобальному розумінні володіє набагато більшим змістом та можливостями, аніжпросте розуміння її у контексті лише природоохоронних технологій. Ми знов звертаємо увагунаукової спільноти, що спрощене копіювання та нарощення нових сенсів у екології, можестворити проблему викривлення змісту предмету, що у свою чергу, веде до чистої демагогії, тадо спрощення розуміння предмету та об’єкту екологічних досліджень. Ми наголошуємо навведенні до наукового використання такого концепту, як «Екологічна футурологія», задопомогою якого буде створене дослідницька площа для моделювання стратегій майбутнього .Ключові слова: Гиперсистема, Екологія, Філософія екології, Футурологія, Екологічнафутурологія, Історія науки та техніки, Техніка, Соціосфера, «Споживацьке існування», Конфлікт.Godz N.B. Ecology’s knowledge and The Futurology in context The Science and questions ofmanagement. The author tries to determine the interconnection and mutual influence of Philosophy andEcology. We continue defending several statements. The first one is based upon the accentuation of astrict system which accepts as valid ones different definitions of Ecology. These definitions aremultidirectional proceeding from the time of their origin, and consequently they are defined through thesphere they serve. But Ecology in the global sense cannot be restricted to environmental protectiontechnologies. It is not the main purpose of Ecology to fight for “purity of environment”. On the whole theinterests of Ecology lie in the parameters of growth, limits of existence, analysis of populations and foodchains. It can be said that Ecology is a science about the system as it is. But adding new meanings andcontents plays not only a positive role, but also a negative one, creating a field of conflicts which can bebased on different understanding of the subject and object of Ecology which can cause demagogy andoversimplicity. Secondly, after considering Ecology knowledge system, we insist on the necessity tointroduce such a concept as Ecological Futurology which can reflect all the practical and theoreticalstrategies of the future of both scientific, technical society as a social hypersystem and Nature as abiological unique system comprising every single living organism and individuals including Man.The approach to technological determinism in the sphere of human life purposes should bereconsidered. The question arises regarding “the improvement” of human life. The current situationreveals the tragic substitution of genuine goals for “consumer existence”. There arises a range ofproblems which grows deeper by means of language limitations, hermeneutic peculiarities – the problemwhich is caused by mistranslation from European languages, e.g. the concept of sustainable development- «Устойчивое развитие» in Russian and «Сталий розвиток» in Ukrainian. To be fair we should addthat new synonymous concepts are being looked for this word combination in Ukrainian now. But theproblem of understanding stays – for some reason development is rendered as economy, stability andeven a stop.Key words: Hypersystem, Ecology, Philosophy of Ecology, Futurology, Ecological Futurology,History of Science and Technology, Technology, Sociosphere, “consumer existence”, Conflict.